The Relationship of Obesity with Range Of Motion (ROM) On The Ankle - Indriyani Indriyani; Mellyana Cahyadi (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Introduction. Obesity is weight gain beyond the limits of physical and skeletal needs due to excessive accumulation of body fat that may increase risk factors for musculoskeletal disorders. A musculoskeletal disorder that can occur is a limited range of motion of a joint. This study aimed to identify the relationship between obesity and ankle range of motion (ROM). Methods. This study was conducted using an analytical observational study with an overall sample of 311 students who met the inclusion criteria. The sample for this study was students’ class of the Muhammadiyah Palembang's School of Medicine from 2018 to 2020 and was extracted using the total extraction method. The population of this study is Palembang students. Results. The study found that 238 students (76.5%) were not obese and 65 students (20.9%) were obese. Among obese college students, 51 college students (69.9%) had normal dorsiflexion ROM and 22 college students (30.1%) had abnormal dorsiflexion ROM. Obese students had normal plantarflexion ROM in her 20 students (27.4%) and students with abnormal plantarflexion ROM in her 53 students (72.6%). 195 students (81.9%) had normal dorsiflexion ROM and 43 students (49.7%) had abnormal dorsiflexion ROM. 185 students (77.7%) had normal plantarflexion ROM and 53 students (22.3%) had abnormal plantarflexion ROM. Conclusion. Suggesting an association between obesity and the Range of Motion (ROM) in the ankle joint.